A COMPARATIVE STUDY ON FOREST WILDFIRE RISK MITIGATION AND MANAGEMENT IN INDONESIA AND UNITED STATES (CASE STUDY: JAMBI AND CALIFORNIA) - Fadiah Izzah Ajrina (Republic of Indonesia Defense University, 2023)
It has been known globally that Indonesia has the largest forest area in the world and is often called as World’s lungs. However, wildfire disasters in Indonesia’s forests are happening every year in various locations. This paper will study the cases by focusing on a case study in Jambi Province and compare it with similar issues that happened in California, United States. The paper shows that various human activities are the main factor in how the accident has happened over the last couple of years. Non-environmental-friendly Activities such as illegal logging and fire land clearing for palm oil plantations have been conducted by private institutions and causing long-lasting impacts on local communities. The poor knowledge of local people on how to prevent and handle wildfire forests also has become an issue that needs to be solved as soon as possible. Compared with what happened in California, the main causes are different considering the fires are caused by high temperatures and climate change’s impact. Although the local community in California barely participates in fire management, the mitigation and monitoring infrastructure is much more advanced compared to Indonesia’s.